Alignment in ASR and L1 Listeners’ Recognition of L2 Learner Speech: French EFL Learners & Dictation.Io - Vincent Chanethom; Alice Henderson (Research in Language)
This study is an extension of Inceoglu et al.’s (2023) study on Google Voice Typing as a pronunciation learning tool. We used the Automatic Speech Recognition (ASR) tool on the dictation.io website (Agarwal, 2022), and our participants were L2 English learners of a different L1, but similar proficiency level. Twelve L1 English listeners assessed the L2 English from four L1 French speakers in terms of intelligibility and comprehensibility, measured by word transcription and Likert scale ratings respectively. Their scores were compared to ASR output. The goal was to determine how accurate the tool is, and to what extent its accuracy correlates with human listeners. The results were generally consistent with those of Inceoglu et al. (2023), with few exceptions which we discuss in the current study.